Description of Compliance With Drugs in Schizophrenia Patients in A Mental Hospital Bali Province Bangli Regency - Anugrah Pradita, Sang Kompiang Irpan; Kusuma Wardani, Ida Aju; Sri Wahyuni, Anak Ayu; Jaya Lesmana, Cokorda Bagus (E-Jurnal Medika Udayana; Vol 12 No 11 (2023): E-Jurnal Medika UdayanaDO - 10.24843/MU.2023.V12.i11.P14, 2023)
Schizophrenia is a psychotic disorder characterized by disturbances that occur in the mind that cause disharmony thought processes, divided soul, erroneous and inappropriate perception attention, and impaired motor activity that shows behavioral changes. Schizophrenia is divided into two groups, namely positive and negative symptoms. Positive symptoms present delusions and hallucinations, while negative symptoms present withdrawn behavior and self-isolation. This study aims to determine the preference for taking medication in patients. This research is qualitative descriptive study. The population is respondents from patients family who responsible to answer questions submitted. Samples taken with purposive sampling technique in inpatient room Nakula and Kunthi Bali Province Mental Hospital with total 10 patients who were the looked for patients in charge. Data collection was carried out by in depth interviews according to inclusion and exclusion criterion, direct interviews with patient’s family members were carried out with a questionnaire guideline. From the results of the study, it’s found that the level of family knowledge was still low about schizophrenia which caused patients not complete take the medication. This is because too many drugs are consumed, the relationship between health professionals and the health system is poor, also relationship between the care giver and the patient is bad, the culture that’s internalized by the family causes differences in perception, and low adherence to medication rules. From the results of the study, it can be said that medication adherence in patients is still low due to the level of family knowledge about schizophrenia.